2014
DOI: 10.1136/bmjopen-2013-004560
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for exposure of glaucoma drainage devices: a retrospective observational study

Abstract: ObjectivesThe purpose of this study was to identify risk factors for exposure of glaucoma drainage devices (GDD).SettingThis retrospective, observational study was conducted in the eye clinic of an academic medical centre.ParticipantsParticipants included 1073 consecutive adults who underwent GDD surgery between 1 January 2005 and 1 January 2011. Participants were included if chart review indicated GDD surgery during the study period and excluded if at least 12 months of clinical follow-up was not available in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
51
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 18 publications
2
51
2
3
Order By: Relevance
“…Follow-up in our study is probably adequate, and is substantially longer compared with a previous report in the Chinese literature, 13 as the median and mean time to exposure has been determined between 8.3 to 14.4 months and 23 to 31 months in the previous studies. 10,21 In our cohort the single case of tube/plate exposure was discovered at the 1-month postoperative visit. A large meta-analysis determined a 2.0 ± 2.6% incidence of tube exposure after an average follow-up of 26.1 ± 3.3 months.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Follow-up in our study is probably adequate, and is substantially longer compared with a previous report in the Chinese literature, 13 as the median and mean time to exposure has been determined between 8.3 to 14.4 months and 23 to 31 months in the previous studies. 10,21 In our cohort the single case of tube/plate exposure was discovered at the 1-month postoperative visit. A large meta-analysis determined a 2.0 ± 2.6% incidence of tube exposure after an average follow-up of 26.1 ± 3.3 months.…”
Section: Discussionmentioning
confidence: 92%
“…8 A number of causes for tube/plate erosion have been postulated including immunemediated inflammation causing patch graft melting, excessive tension or mechanical friction of tissue, poor perfusion, and ischemic damage to the conjunctiva. [9][10][11] Conjunctival erosion and GDD exposure requires immediate surgical repair, which is, however, challenging and may require multiple additional revisions after the initial repair and implant removal in a substantial proportion of cases. 12 The purpose of this pilot study was to determine the safety and efficacy of fresh, human donor cornea-sclera obtained immediately after keratoplasty, as patch graft material in GDD surgery.…”
mentioning
confidence: 99%
“…It has been reported that no material used for ADD tube coverage is more prone to erosion than another, including sclera, tutoplast sclera, dura, and tutoplast pericardium. 24,27 However, in a large comparative case series, Zalta 17 found that sclera eroded significantly faster than dura after ADD surgery, though the PGF rate suggested that dura and sclera tissues are equally successful in 94% of ADD surgeries. In the study by Wigton et al 9 the glycerol-preserved cornea group presented a significantly lower PGF rate (1.9%, mean follow-up of 14.5 months) compared with the pericardium group (8.9%, mean follow-up of 11.0 months).…”
Section: Discussionmentioning
confidence: 99%
“…A mechanical contribution is also possible as reported in later shunt erosions [3,4]. Uveitis was reported to not significantly increase the chronic risk for shunt exposure [5]. However, early tube erosion in an inflamed eye was previously described [3].The patch graft was positioned bevel and parallel to the shunt ridge as well as covered the adjacent shunt tube to reduce mechanical forces upon the transposed conjunctiva.…”
Section: Discussionmentioning
confidence: 99%